1993
DOI: 10.1017/s0142716400009541
|View full text |Cite
|
Sign up to set email alerts
|

Phonological and morphological awareness in first graders

Abstract: Phonological awareness is thought to be related to children's success in learning to read because it indicates an awareness of the internal structure of words. Morphological awareness, which has been found to be related to reading achievement for older students, may offer a more comprehensive measure of linguistic sensitivity because it entails not only phonological awareness, but also other aspects of linguistic knowledge. The research study reported herein was designed to investigate the extent to which phon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
182
1
21

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(222 citation statements)
references
References 25 publications
17
182
1
21
Order By: Relevance
“…However, the research evidence into the role of grammatical awareness in early reading skills tends to be highly inconsistent. While some have reported small but reliable relationships (Carlisle, 1995;Carlisle & Nomanbhoy, 1993), others have found the effect of grammatical skills on reading to be either unreliable (Muter, et al, 2004) or indirect through its relationship with the phonological skills (Nikolopoulos, et al, 2006;Silven, et al, 2007). We now turn to the link between grammatical skills and spelling.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…However, the research evidence into the role of grammatical awareness in early reading skills tends to be highly inconsistent. While some have reported small but reliable relationships (Carlisle, 1995;Carlisle & Nomanbhoy, 1993), others have found the effect of grammatical skills on reading to be either unreliable (Muter, et al, 2004) or indirect through its relationship with the phonological skills (Nikolopoulos, et al, 2006;Silven, et al, 2007). We now turn to the link between grammatical skills and spelling.…”
mentioning
confidence: 87%
“…These findings should be evaluated with the recognition that morphological and phonological skills often show strong covariance suggesting reciprocal relationships between 8 these two linguistic skills and this can complicate a coherent analysis of their unique predictive role in literacy skills (Carlisle, 2000;Carlisle & Nomanbhoy, 1993). Furthermore, in agglutinative languages like Finnish and Turkish, the suffixation process draws the attention of the children to the final phoneme and internal phonemic structure of words, which can facilitate the development of phonological awareness skills (Durgunoğlu & Öney, 1999;Lyytinen & Lyytinen, 2004).…”
mentioning
confidence: 99%
“…Early MA acquisition has been shown to be dependent on an individual's prereading PA, independent of vocabulary (Carlisle and Nomanbhoy, 1993;Cunningham and Carroll, 2015;Law et al, 2016). Chiat (2001) argued that as children are exposed to speech in context, they segment the target speech stream into available phonological components, which are capable of being generalized or related to the context at hand.…”
Section: Impact Of Phonological Awareness On Early Morphological Awarmentioning
confidence: 99%
“…Studies have demonstrated that more complex phonological shifts between base and derived form are unattainable for many children first learning to read (e.g. divide and division, invade and invasion), while gains in PA and an increased sensitivity to the phonemic structure of language aid in the learning of morphophonemic rules, thus furthering morphological learning (Carlisle & Nomanbhoy, 1993). (Cavalli et al, 2016;Law et al, 2015).…”
Section: Impact Of Phonological Awareness On Early Morphological Awarmentioning
confidence: 99%
“…Some of the most significant findings that have accumulated over the years include the following: pre-school children and first-graders have poor ability to produce appropriate derived forms (Berko 1958, Carlisle andNomanbhoy 1993); fourth-graders can recognize base morphemes in unfamiliar derivatives (Tyler and Nagy 1989), while eighth-graders can recognize the relationship between low frequency words and their suffixed derivatives (Wysocki and Jenkins 1987). According to Nagy et al (1993) mastering the use of affixation may continue well into high school, yet even adult native speakers seem to have incomplete knowledge of derivational morphology (Schmitt and Zimmerman 2002).…”
Section: Introduction: the Nexus Between Vocabulary And Morphologymentioning
confidence: 99%